2006
DOI: 10.1111/j.1365-2044.2006.04703.x
|View full text |Cite
|
Sign up to set email alerts
|

Does the efficacy of supplemental oxygen for the prevention of postoperative nausea and vomiting depend on the measured outcome, observational period or site of surgery?

Abstract: SummaryHigh intra-operative oxygen concentration reportedly reduces postoperative nausea and vomiting (PONV), but recent data are conflicting. Therefore, we tested whether the effectiveness of supplemental oxygen depends on the endpoint (nausea vs. vomiting), observation interval (early vs. late) or surgical field (abdominal vs. non-abdominal). We randomly assigned 560 adult patients undergoing various elective procedures with a PONV risk of at least 40% to intra-operative 80% (supplemental) or 30% oxygen (con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 28 publications
0
28
0
1
Order By: Relevance
“…Furthermore, a large study involving 560 patients investigating the impact of O 2 on PONV concluded it has no impact on PONV regardless of the site or surgery or the observational period (early or late PONV). 33 In conclusion, we demonstrated that 70% N 2 O increases the incidence of nausea and severity of nausea at 24 h after laparoscopic gynecological surgery in the absence of any prophylactic antiemetic. This preliminary finding indicates that N 2 O may increase PONV in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, a large study involving 560 patients investigating the impact of O 2 on PONV concluded it has no impact on PONV regardless of the site or surgery or the observational period (early or late PONV). 33 In conclusion, we demonstrated that 70% N 2 O increases the incidence of nausea and severity of nausea at 24 h after laparoscopic gynecological surgery in the absence of any prophylactic antiemetic. This preliminary finding indicates that N 2 O may increase PONV in a dose-dependent fashion.…”
Section: Discussionmentioning
confidence: 52%
“…Eleven trials (2,293 patients) reported dichotomous data on presence or absence of nausea or vomiting (table 2). 6,7,27,29,30,57,59,65,67,68,71 When combining all data, only prevention of late nausea showed statistical significance in favor of high FIo 2 ( fig. 3A).…”
Section: Perioperative Medicinementioning
confidence: 98%
“…7,15,23 Other interventions that may be helpful are preoperative hydration, aggressive fluid replacement for blood loss, stimulation of acupuncture point P6, music therapy, and aromatherapy. 18 Analysis of data 30,31 on the efficacy of intraoperative supplemental oxygen in the prevention of PONV has been conflicting, and this intervention currently is not recommended.…”
Section: Prophylaxis Therapiesmentioning
confidence: 99%